The Alterations of Serum IgG Fucosylation as a Potential Additional New Diagnostic Marker in Advanced Endometriosis - Sołkiewicz K; Krotkiewski H; Jędryka M; Czekański A; Kratz EM (Dove Medical Press, 2022)
Katarzyna Sołkiewicz, 1 Hubert Krotkiewski, 2 Marcin Jędryka, 3, 4 Andrzej Czekański, 3, 4 Ewa Maria Kratz 1 1Department of Laboratory Diagnostics, Division of Laboratory Diagnostics, Faculty of Pharmacy, Wroclaw Medical University, Wroclaw, 50-556, Poland; 2Hirszfeld Institute of Immunology and Experimental Therapy, Polish Academy of Sciences, Wroclaw, 53-114, Poland; 3Department of Oncology, Gynecological Oncology Clinic, Faculty of Medicine, Wroclaw Medical University, Wroclaw, 53-413, Poland; 4Department of Oncological Gynecology, Wroclaw Comprehensive Cancer Center, Wroclaw, 53-413, PolandCorrespondence: Ewa Maria KratzDepartment of Laboratory Diagnostics, Division of Laboratory Diagnostics, Faculty of Pharmacy, Wroclaw Medical University, Borowska Street 211A, Wroclaw, 50-556, PolandTel +48 71 784 01 52Fax +48 71 784 01 54Email ewa.kratz@umw.edu.plBackground: Endometriosis is an inflammatory disease leading to the growth of endometrial-like tissue outside of the uterus, which affects approximately 10% of young women of reproductive potential. The diagnosis of this disease is difficult, often invasive and time-consuming, therefore non-invasive diagnostic methods are strongly desirable in endometriosis detection. The aim of our project was to investigate whether any associations exist between the expression of serum IgG fucosylation and advanced stages of endometriosis. We were also interested in whether native serum IgG (s-IgG) fucosylation analysis, without prior IgG isolation, could provide a panel of parameters helpful in non-invasive diagnostics of advanced endometriosis.Methods: IgG fucosylation was examined using a lectin-ELISA test with fucose-specific lectins: AAL and LCA, specific for core fucose α 1,6-linked, as well as LTA and UEA which recognize α 1,3- and α 1,2-linked fucose, respectively.Results: ROC curve and cluster analysis showed s-IgG reactivities with the panel of fucose-specific lectins AAL, LCA and LTA.Conclusion: s-IgG reactivity with the panel of fucose-specific lectins AAL, LCA and LTA can be taken into account as a useful diagnostic and clinical tool to differentiate women with advanced endometriosis. Moreover, it has been shown that the analysis of native IgG fucosylation directly in serum, without prior time-consuming, expensive IgG isolation, is sufficient to distinguish advanced stages of endometriosis from a control group of healthy women.Keywords: serum IgG, IgG fucosylation, lectin-ELISA, endometriosis